2017
DOI: 10.21767/2171-6625.1000213
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic Pattern and Severity Grading Scale of Carpal Tunnel Syndrome in Sudanese Patients

Abstract: Background: Carpal tunnel syndrome is the most frequent compression-induced neuropathy, where the median nerve is compressed at the wrist causing sensory and motor deficits. It is more common in females than males and accounts for a higher number of days off work than all other work-related musculoskeletal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Abdalla, S.F. et al (2017) in their study stated that out of 671 patients with CTS, paresthesia was reported by 339 patients (70%) 8 .…”
Section: Discussionmentioning
confidence: 95%
“…Abdalla, S.F. et al (2017) in their study stated that out of 671 patients with CTS, paresthesia was reported by 339 patients (70%) 8 .…”
Section: Discussionmentioning
confidence: 95%
“…Aygül et al found a significant delay in F latencies with progressive disease in their study of 57 patients [ 14 ]. Another comprehensive investigation into subgroups revealed a decrease in F-wave conduction velocity, correlated with disease severity [ 15 ]. However, the latter study lacked a detailed analysis of the precise stage at which sensitivity begins.…”
Section: Discussionmentioning
confidence: 99%
“…CTS can occur at any age, but its peak incidence is between 40 and 50 years. Women are also 10 times more prone to this disease than men [ 5 , 6 ]. Although the etiology of CTS is unknown, there are a number of risk factors, including diabetes mellitus, thyroid disease, wrist fracture, rheumatoid arthritis, amyloidosis, acromegaly, and also age and female gender [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%